Amylin and its analogs: a friend or foe for the treatment of Alzheimer's disease? - Qiu, Wei Qiao; Zhu, Haihao (Frontiers in Aging Neuroscience, 2014)
Amylin, a gut-brain axis hormone, and amyloid-beta peptides (Aβ), a major component of the Alzheimer’s disease (AD) brain, share several features, including similar β-sheet secondary structures, binding to the same receptor and being degraded by the same protease, insulin degrading enzyme (IDE). However, while amylin readily crosses the blood brain barrier (BBB) and mediates several activities including improving glucose metabolism, relaxing cerebrovascular structure, modulating inflammatory reaction and perhaps enhancing neural regeneration, Aβ has no known physiological functions. Thus, abundant Aβ in the AD brain could block or interfere with the binding of amylin to its receptor and hinder its functions. Recent studies using AD animal models demonstrate that amylin and its analog reduce the AD pathology in the brain and improve cognitive impairment in AD. Given that, in addition to amyloid plaques and neurofibrillary tangles, perturbed cerebral glucose metabolism and cerebrovascular damage are the hallmarks of the AD brain, we propose that giving exogenous amylin type peptides have the potential to become a new avenue for the diagnosis and therapeutic of AD. Although amylin’s property of self-aggregation may be a limitation to developing it as a therapeutic for AD, its clinical analog, pramlintide containing 3 amino acid differences from amylin, does not aggregate like human amylin, but more potently mediates amylin’s activities in the brain. Pramlintide is an effective drug for diabetes with a favorable profile of safety. Thus a randomized, double-blind, placebo-controlled clinical trial should be conducted to examine the efficacy of pramlintide for AD. This review summarizes the knowledge and findings on amylin type peptides and discuss pros and cons for their potential for AD.